Environmental & architectural phenomenology. Vol. 11, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 2000)
Vol. 11, No. 2, Spring 2000 (includes “items of interest,” "citations received,” book reviews of Yi-Fu Tuan's Escapism & Gary Coates' book on Scandinavian architect Erik Asmussen, essay by Richard Capobianco, and introduction to the new reprint edition of Dwelling, Place and Environment).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals